Social Movements and Film - Sissenich, Beate (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course explores social movements of race and ethnicity, class, and gender in the US and other countries. Through academic writings and films, we will investigate why movements emerge when they do, what forms they take, and what outcomes they produce. What does it take to generate sustained political contention? What makes individuals join protests? And why do some situations not generate any contentious action at all, even if they seem to cry out for mass protest? Why are some movements local, while others spread across many countries? Why are some movements peaceful, whereas others resort to violence? How do relations between the state and society change in the course of contentious action? Case studies will include organized racism, the US civil rights movement, labor, the Chinese democracy movement, Islamic activism, and anti-colonialism. The case material covers democratic and non-democratic forms of government, as well as a range of conflict dimensions such as race, class, and gender. Special attention will be paid to social movement tactics, especially the decision to use violence.